TINJAUAN MASLAHAH TERHADAP PRAKTEK PELAKSANAAN BIMBINGAN PERKAWINAN - Syamsul Maarif (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
This study aims to determine the implementation of marriage guidance in an effort to minimize the divorce rate in the perspective of maslahah mursalah. The author will describe several factors that hinder and support the implementation of marriage guidance programs and how to review the problem of mursalah on the implementation of marriage guidance in an effort to minimize the increase in divorce rates. This research is qualitative research (Field Research). The author in obtaining data uses three data collection techniques, namely interviews, observation and documentation. The author uses data analysis techniques in the form of objective interpretations. From the results of this study in its implementation, it is clear that every activity has factors that become obstacles and supporting factors. We know that the KUA of Tembelang District has been as good as possible in the success of the program from the government to help prospective couples who will get married in preparing mentally as a provision for themselves well before entering married life, namely by holding a marriage guidance program. However, there is still a lot of interest in awareness of the importance of the program from some prospective couples who will get married is a factor inhibiting the activity itself. Marriage guidance in KUA Tembelang District meets the requirements in the formation of activities adhering to the perspective of maslahah mursalah, marriage guidance in KUA Tembelang District has had a very large positive impact and benefits for the community around Tembelang District and also the surrounding area, especially couples who want to get married in KUA Tembelang District. Marriage guidance in KUA Tembelang District is not found specifically in the Qur'an or Hadith, but in the formation of activities and the implementation of the program does not contradict the legal order or the basis of nash decrees and provides benefits to the community and prevents madlorota Marriage guidance in KUA Tembelang District is not found specifically in the Qur'an or Hadith, but in the formation of activities and the implementation of the program does not contradict the legal order or the basis of nash decrees and provides benefits to the community and prevents madlorotan.